Hand grip strength in institutionalized older adults with osteoarticular diseases - Garbin, Karina (2022)
Chronic osteoarticular diseases, such as rheumatism and osteoporosis, increase in prevalence with aging, especially in long-term institutions. These musculoskeletal complications can affect the individual’s manual grip strength and consequently their functional capacity, independence and quality of life. Hence, this study evaluates the hand grip strength of institutionalized older adults with osteoarticular diseases. A cross-sectional, population-based research was carried out at long-term institutions in Passo Fundo, Rio Grande do Sul, Brazil, between 2016 and 2018. The sample comprised 68 patients, evaluated for sociodemographic and health variables (medical records), cognitive status (Mini Mental State Examination), functional capacity (Katz Index) and manual grip strength (manual dynamometry). Statistical analysis used descriptive statistics, Student’s t-test paired samples and Student’s t-test of independent samples (p ? 0.05). Older adults showed a maximum hand grip strength of 6.60 ± 5.88 kg (right hand: 6.02 ± 5.78 kg; left hand: 4.50 ± 4.47 kg; p = 0.046). Women presented the lowest hand grip strength values observed (maximal and bilateral grip strength), with cognitive decline (maximal grip strength and right hand) or with severe dependence (left hand grip strength) (p ? 0.05). In conclusion, institutionalized older adults with osteoarticular diseases present manual grip strength values much lower than the expected, especially the women, with cognitive decline or with severe functional dependence.